Genetic determination of cardiac mass in normotensive rats: results from an F344xWKY cross. - Sebkhi,A; Zhao,L; Lu,L; Haley,CS; Nunez,DJ; Wilkins,MR (Hypertension, 1999)
Genetic determinants affect adult cardiac mass and the predisposition to develop cardiac hypertrophy. The aim of this study was to identify quantitative trait loci (QTL) that control heart and left ventricular (LV) weight by use of normotensive inbred rat strains that differ in their adult cardiac mass phenotype. We studied 126 male F2 rats derived from a cross of normotensive Wistar-Kyoto and Fischer 344 rats. At 12 weeks of age, total heart weight and LV weight were measured. Genomic DNA from these animals was screened by use of polymorphic microsatellite markers across the whole genome (excluding the sex chromosomes). In this cross, the genetic contribution to total heart weight variation was 56%, and the genetic contribution for LV weight was 55%. Using the Mapmaker/QTL computer package, we identified a significant QTL on chromosome 3 with a log10 likelihood (LOD) score of 4.8, which accounted for 16.5% of the total variance of LV weight. This QTL was centered close to the marker D3Rat29. The QTL was also found to be significantly linked with total heart weight (LOD=4.4). These data provide the first demonstration of a QTL on chromosome 3 that plays a role in determining the difference in LV mass between normotensive Fischer 344 and Wistar- Kyoto inbred rat strains. The prostaglandin synthase 1 gene is located within the QTL.